A SURVEY OF WEB TECHNOLOGIES USED IN INDONESIA LOCAL GOVERNMENTS - Rakhmawati, Nur A; Harits, Sayekti; Hermansyah, Deny; Furqon, Muhammad Ariful (Department of Information Systems, Institut Teknologi Sepuluh Nopember, 2018)
Indonesia has 548 local governments (34 provinces, 349 cities and 91 municipalities). One of implementation of egovernment is providing local government information through an official website. Therefore, we investigate 548 official websites of local government in Indonesia including a list of web technologies such as web server, web programming, CSS framework, Content management system, web framework and web 3.0. To collect data about local government websites, we did a survey with the help of Wappalyzer. Each website should be visited and checked by Wappalyzer. In general, the technologies used in official local government website are the widely known in the world as well. There is a lack of implementation of web 3.0 to build Indonesia local government, particularly in governmentrelated vocabularies.